2011
DOI: 10.1021/ie200487g
|View full text |Cite
|
Sign up to set email alerts
|

2-Acetylpyridine-N(4)-Morpholine Thiosemicarbazone (HAcpMTSc) as a Corrosion Inhibitor on Mild Steel in HCl

Abstract: 2-Acetylpyridine-N(4)-morpholine thiosemicarbazone (HAcpMTSc) was synthesized and investigated as an inhibitor for mild steel corrosion in acid media. Various concentrations of the inhibitor in 1 M HCl solution were tested, and the corrosion inhibition efficiency to mild steel was estimated by means of weight loss measurements, potentiodynamic polarization, and electrochemical impedance spectroscopy. The adsorption equilibrium constant (K ads ) and standard free energy of adsorption (ΔG°a ds ) were calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…This remarkable improvement could be due to the synergistic adsorption of FYPA and iodine ions. As expected, the C dl value tended to decrease in the presence of FYPA and combination with KI, resulting from a decrease of the local dielectric constant or the increase of the thickness of the electrical double‐layer capacitor . The results revealed that the inhibitor molecules were adsorbed on the steel surface acting at the interface electrode and solution.…”
Section: Resultssupporting
confidence: 61%
“…This remarkable improvement could be due to the synergistic adsorption of FYPA and iodine ions. As expected, the C dl value tended to decrease in the presence of FYPA and combination with KI, resulting from a decrease of the local dielectric constant or the increase of the thickness of the electrical double‐layer capacitor . The results revealed that the inhibitor molecules were adsorbed on the steel surface acting at the interface electrode and solution.…”
Section: Resultssupporting
confidence: 61%
“…In addition, multiple bonds or aromatic rings can block the active corrosion sites on the metal surface. 5,6 Corrosion inhibitors are found to protect steel corrosion in acid solutions by adsorbing onto steel surfaces. Adsorption is a separation process involving two phases between which certain components can become differentially distributed.…”
Section: Introductionmentioning
confidence: 99%
“…So the inhibition efficiency increases with the lengthening hydrophobic chain. Considering the effect of inhibitors on capacitance, a substantial decrease in Cdl can be observed and the double‐layer capacitance can be expressed as follows: italicCdl=italicY0(italicωmax)n−1,where ωmax is the frequency at which the imaginary part of the impedance is at maximum. Generally, the decrease in Cdl is due to the reducing local dielectric constant for the displacement of water and/or thickening electric double layer .…”
Section: Resultsmentioning
confidence: 99%